Transverse craniofacial dimensions in Angle Class II, Division 1 malocclusion according to breathing mode - Agda Rísia David Pinto Coelho; Orlando Tanaka; Jucienne Salgado Ribeiro; Maria Ângela Naval Machado; Elisa Souza Camargo (Sociedade Brasileira de Pesquisa Odontológica, 2010)
The aim of this longitudinal study was to assess the relation between the transverse craniofacial dimensions of subjects with Class II, Division 1 malocclusion and the breathing mode presented by them. Forty Angle Class II, Division 1 malocclusion subjects of both genders participated in the study, 23 of which were predominantly nose breathers and 17 were predominantly mouth breathers. The mean age ranged from 10 years and 9 months to 14 years - Age range 1; and from 13 years and 4 months to 16 years and 6 months - Age range 2. Measurements of six transverse craniofacial dimensions were performed in P-A teleradiographs: Total Sphenoid, Total Zygomatic, Total Nasal Cavity, Total Maxilla, Total Mastoid and Total Antegonion. The transversal craniofacial dimensions were measured and compared in both groups at age ranges 1 and 2. The longitudinal assessment of age ranges 1 and 2 showed that there was no statistically significant influence of the breathing mode on the craniofacial dimensions evaluated, or on the alteration of these dimensions. Breathing mode had no influence on craniofacial development in the sample studied.